Intensity modulator for secure, stable, and high-performance decoy-state quantum key distribution - Feng-Yu Lu (Nature Portfolio, 2021)
Abstract The decoy-state method substantially improves the performance of quantum key distribution (QKD) and perfectly solves crucial issues caused by multiphoton pulses. In recent years, the decoy-state method has occupied a key position in practicality, and almost all the QKD systems have employed the decoy-state method. However, the imperfections of traditional intensity modulators limit the performance of the decoy-state method and bring side channels. In this work, a special intensity modulator and its accompanying modulation method are designed and experimentally verified for the secure, stable, and high-performance decoy-state QKDs. The experimental result indicates that its stable and adjustable intensities, convenient two-level modulation, inherently high speed, and compact structure is extremely fit for future trends and will help the decoy-state method to be perfectly applied to QKD systems.